Authority Of The Internal Investigating Prosecutor Make Arrest And Detention Performers Of Criminal Acts Of Corruption - I Made Wahyu Chandra Satriana; Ni Made Liana Dewi; Ni Putu Ari Seni Antari (Universitas Dwijendra Press, 2023)
Described problems in this research is what does the legal basis of the inventory in arrest and detention the corruptor. The objectives of this research is to know the legal basis of investigators in creating and handling the corruptor, and to know the obstacles contained incidence principles in catching and handling the corruptors. The research method used in this study is the normative juridical which is a study that refers to legal analysis. The approach in this study emphasizes the legislation approach that is the search for some legislation related to the investigation of corruption crime. The result of the research is indicate the normative juridical basis of the authority of the prosecutor in conducting arrest and detention in accordance to with article 16th KUHAP and article 20th KUHAP. Regarding the obstacles on the implementation of arrest and detention perfomance is related to the time of arrest the geographical position if indonesian associated shall create problems that does not allow the arrest within one day, other factors are the suspects escape and the dificulty to done so that inhibit persuit investigation process. Obstacles to detention may also be encountered by a suspect who refuses detention and insists not to be detained, the suspect flees and does not meet the conditoins of detention in article 21th KUHAP.